Timur dönemi sanatında Kemal’üd Din Bihzad - Ersoy, Nilüfer (My University, 2021)
Tarihte nadir rastlanan bir iktidara sahip; hükümdar ve yöneticilerinin hepsinin sanatsever, sanatçı ve bilim adamı olan Timurlu İmparatorluğu, 1370 yılında Emir Timur tarafından kurulmuş ve kısa bir süre içerisinde çok geniş bir coğrafyaya yayılmıştır. Timur kazandığı savaşlarda bölgedeki bilim insanlarını, alimleri, sanatçıları, zanaatkarları ve bütün iş kollarındaki en iyi kişileri kendi başkentine taşımış; kurduğu devleti ileri seviye bir kültür ve sanat merkezi haline getirmeyi hedeflemiştir. Timur’un vefatından sonra taht kavgaları başlamış dış ülkelerin de baskıları ve saldırıları sonucunda İmparatorluk giderek küçülmüştür. Bu olumsuzluklara rağmen kültür-sanat alanındaki çalışmalar, hükümdar ve yöneticiler tarafından desteklenmiş, sanatçılara ve alimlere en iyi çalışma imkanları sunulmuştur. Timurlu İmparatorluğu’nun son parlak dönemi olan Hüseyin Baykara zamanında kitap sanatları tam olgunluk çağına girmiş, çok üstün sanatçılar yetişmiş ve muhteşem eserler üretilmiştir. Bu sanatçılardan biri de olağanüstü tasarım gücüne, hayal gücüne, gözlem yeteneğine sahip; minyatür sanatına realist ve natüralist bir anlayış ekleyip yeni bir yön veren, ressam Üstad Kemal’üd Din Bihzad’dır. Minyatür alanında çok büyük yenilikler yaparak bu sanatı en üst seviyeye getirmiştir. Ölümünden sonra yetiştirmiş olduğu öğrencileri minyatür sanatını ileriye taşımaya devam etmişlerdir.

The Timurid Empire; which was a unique potency and sovereignty in History where all its emporers and governers were such artists, artlovers and scientists was established in 1370 by Emir Timur and expanded its lands in to a very wide geography in a very short time of period.Emperor Emir Timur moved all the scientists, artists, artisans, intellectuals, craftsman and the experts who were the best ones in their own business areas to his capital city after the wins of war and targeted to bring his country in to an advanced level of culture and fine arts as a kind of art center.After his death; the hassels of throne had started and in addition to that following the attacks and the political&ecomomical threat of other countries take part; the country’s borders started to shrink.Eventhough the negative impact of said situations; the support of the emperors and governors related to the fine art and cultural works continued and they provided the suitable facilities and oppurtunities to those artists, scientist and the intellectuals. In the period of Hüseyin Baykara which was the last shiny and glorious times of the Timurlu Empire; the art works for literature reached its matured level and let grew lots of distinguished and talented artists and so many magnificent creations and productions had been made.One of the said period’s distinguished artist was the painter Master Kemal’üd Din Bihzad who had an extraordinary and remarkable imagination, conception and observation power for design works and led the direction of art Miniature with a new perspective in terms of realistic and naturalistic understanding. In that era the Master Kemal’üd Din Bihzad carried forward the level of art Miniature with drastic developments. The pupils those had been raised by Master contuniued to develope his art after death.
Keywords: Bihzad; Elyazması; Fine arts education; Güzel sanatlar eğitimi; Herat; Herat Ekolü; Herat School; History; Huseyin Baykara; Hüseyin Baykara; Manuscript; Manuscripts; Miniature; Miniature painting; Minyatür; Minyatür resim; Tarih; Timur Dönemi; Timurid Period; Timurids; Timurlar; Timurlular; Yazma Eserler Bihzad